Agency theory and managerial ownership: evidence from Malaysia - Mustapha, Mazlina; Che Ahmad, Ayoib (Emerald Group Publishing, 2011)
Purpose: The purpose of this paper is to investigate the effect of managerial ownership in relation to agency theory in the Malaysian business environment. In addition to examining the total managerial shareholdings, this study also investigates the association between direct and indirect managerial shareholdings with agency costs. Design/methodology/approach: The data for the study is obtained from two sources, namely primary (questionnaire) and secondary (annual reports) data. The sample companies are 235 companies listed on Bursa Malaysia for the financial year ended 2006. Multiple regression analysis is used to estimate the relationship between the variables. Findings: The results of the study indicate that managerial ownership in various segments has an inverse relationship with total monitoring costs as predicted in agency theory. This finding is consistent with earlier studies in western countries and supports the convergence of interest hypothesis. Originality/value: This study gives a unique contribution to corporate governance studies relating to the effect of ownership structure in relation to agency theory in Malaysian companies, one of the countries in Asia. Previous studies claimed that it is unknown whether the agency theory findings in western countries have equal impact in Asian organizations. Previous literature also indicates that there is a possibility that given the cultural differences, the typical nature of agents in agency theory may not be the case with regard to non‐western countries. Thus, this study provides evidence that support prior research findings in western countries relating to the effect of managerial ownership on the agency relationship which is reflected in its agency costs.